Norms, Equity and Social Protection: A Gender Analysis of the Productive Safety Net Programme in Ethiopia. Issue 1 (2nd January 2023) - Lemma, Melisew Dejene; Kukem, Tesfaye Semela; Vercillo, Siera; Cochrane, Logan
Abstract: Social protection programmes do not generally account for gendered power dynamics. Oftentimes, they target women only as beneficiaries, which can intensify gendered disparities. This case study uses a mixed methods research approach to conduct a gender analysis of the Productive Safety Net Programme in Ethiopia. We find the programme has progressive gender equity goals, but these are not well implemented. Since special provisions for women are neglected in the case study sites, they do not challenge unequal social norms nor recognize unequal roles and responsibilities. Alongside implementing the gendered provisions, we recommend further research into the ways that the programme can challenge discriminatory social norms.